Availability, use, and affordability of medicines in urban China under universal health coverage: an empirical study in Hangzhou and Baoji - Yunyu Huang; Youfen Jiang; Luying Zhang; Wenhui Mao; Job F. M. van Boven; Maarten J. Postma; Wen Chen (BMC Health Services Research, 2018)
Abstract Background This study aimed to examine the availability, use, and affordability of medicines in urban China following the 2009 Health Care System Reform that included implementation of universal health coverage (UHC). Methods This longitudinal study was performed in Hangzhou (high income, eastern China) and Baoji (lower income, western China). Five yearly household surveys were conducted (one each year from 2009 to 2013) to evaluate the impact of UHC on medicines use and expenditure, and a health facility survey was conducted in 2013 to evaluate availability of medicines. A cohort of over 800 households in Hangzhou and Baoji was established in 2009, and 20 hospitals were included in the health facility survey. Medicines use was determined using data from health facility and household surveys. An average, two-week out-of-pocket medicines expenditure was calculated to assess the affordability of medicines. Results The number of medicines stocked in primary health facilities in Hangzhou decreased, while the number in Baoji increased. In Baoji, patients usually chose a pharmacy to buy medicines directly, despite the 48.2% increased availability of essential medicines in primary health care centers. The majority of survey respondents stated that their medicines need was basically met; however, medicines cost still accounted for a major part of their health expenditure. Medicines expenditure showed an increasing trend from 2009 to 2013. The average annual growth rate of household overall medical expenditure was significantly higher than that for household non-food consumption expenditure. Conclusions Following China’s Health Care System Reform and implementation of UHC, availability and use of medicines has improved in urban areas. However, the affordability of medicines is still a concern.